(untitled) (Bangladesh Rice Journal, 2014)
Experiments were conducted at BRRI farm Gazipur during Boro season 2010-12 to determine maximum depth of water level below ground surface in alternate wetting and drying (AWD) method. The experiment was laid out in a randomized complete block design with four irrigation treatments. The treatments of AWD method were: T1 = continuous standing water, T2 = irrigation when water level reached 15 cm below ground level, T3 = irrigation when water level reached 20 cm below ground level and T4 = irrigation when water level reached 50 cm below ground level. The experiment involved BRRI dhan28 as a test crop. The treatment T2 gave the highest grain yield (5.9 and 6.2 ton/ha) in 2010-11 and 2011-12, respectively. Maximum benefits per hectare were found Tk. 5476 and 4931 for using 807 and 880 mm water during 2010-11 and 2011-12 respectively and thus water productivity was 7.1 kg/ha-mm in T2 for both the seasons. Continuous standing (T1) water (1013 and 1100 mm) gave comparable grain yield 5.7 and 6.0 ton/ha in 2010-11 and 2011-12, respectively. Minimum water productivity was found in treatment T1 (5.6 and 5.4 kg/ha-mm) for both the seasons. Application of irrigation when water was 15 cm below soil surface was found most profitable in AWD system and the grain yield was decreased when water level was below 15 cm depth. Therefore, the recommended AWD technology could increase rice yield and save irrigation water by 25-30 percent. DOI: http://dx.doi.org/10.3329/brj.v17i1-2.20899 Bangladesh Rice j. 2013, 17(1&2): 33-37